VD_FINDINFO HC / 2014 / 82 vom 15. Januar 2014 - VD Tribunal cantonal (2014)
PROTECTION DE L'UNION CONJUGALE, GARDE ALTERNÉE, OBLIGATION D'ENTRETIEN | 176 al. 1 CC, 176 al. 3 CC, 308 al. 1 let. b CPC (CH)